Antioxidants in Extra Virgin Olive Oil and Table Olives: Connections between Agriculture and Processing for Health Choices - Barbara Lanza; Paolino Ninfali (MDPI AG, 2020)
This review focuses on the conditions required to increase and maintain the antioxidant nutrients in both extra virgin olive oil (EVOO) and table olives (TOs) from the agronomic and technological practices to the gastronomy. The main antioxidants of TOs and EVOO are phenol alcohols and acids, secoiridoids, lignans and flavones, all of which possess the ability to prolong the oil’s shelf-life and exhibit healthy properties for humans. The precise detection of secoiridoid derivatives remains the breakthrough for the nutritional and health quality certification of extra virgin olive oils (EVOOs) required for EFSA health claims. To attain the necessary antioxidant quality in both EVOO and TOs, it is necessary to hard focus on the several steps in the production chain, including olive cultivar, agronomic conditions, harvesting methods, and transformation technology. The quality level is maintained if the storage conditions aim to minimize the oxidative processes that occur due to oxygen and light. In terms of minor polar biophenols, there is disagreement on which between the organic or conventional EVOOs show higher concentration values. The strict disciplinary of production of protected designation EVOOs does not ensure higher phenol values in comparison to the artisanal EVOOs. In gastronomy, the EVOOs are preferable to seed oils, particularly during frying vegetable. The EVOOs show higher heat stability, linked both to the fatty acid composition and the phenol content, that is important for preventing fatty acids oxidation. Concerning TOs, the commercial presentation includes olives and olive paste. Both products show a remarkable loss of natural antioxidants after pasteurization and during storage as the thermal treatment mostly impacts on TOs secoiridoids.